Electrostatic metallic glass micro-mirror fabricated by the self-aligned structures. (6th March 2020) - Wang, Zhao-Ying; Chen, Yu-Yen; Lin, Yu-Ching; Ono, Takahito; Lin, Ming-Tzer; Tsai, Yao-Chuan
Abstract: In this work, an electrostatic comb-drive micro-mirror with the Pd-based metallic glass torsion bar and the self-aligned structures was proposed and developed. The self-aligned structure of the comb-drive micro-mirror is achieved avoiding the comb structure alignment process. The fixed combs of the top mirror wafer were lifted by the bottom activation post for making the comb height difference. The height difference between the fixed combs and moving combs could effectively increase the torque to the mirror structure. The static tilting angle of 16° was achieved when the input voltage is 45.6 V. In the resonant mode, the scanning angle of 40.5° was achieved when the input voltage is 30 V pp at 95 Hz. According to the measurement results and comparing with other silicon torsion bar micro-mirrors, the driving voltage could be decreased 50% and the tilting angle could be increased around four times for the proposed micro-mirror.